LEGAL STANDING IN ENVIRONMENTAL STATE ADMINISTRATIVE DISPUTES IN INDONESIA - Untoro; Raihan (Cirebon International Conference on Education and Economics Proceeding, 2024)
The right to sue is a determining factor for someone who is in a lawsuit whether they are a legal subject who has fulfilled the requirements or not fulfilled the requirements to file a case before the court in accordance with the provisions of the applicable law. The right to sue is given to three parties, first an individual. Second, business entities incorporated or unincorporated. Third, environmental organizations. The three parties are given the right to file a lawsuit if their interests are harmed by state administrative decisions and or government administrative actions. Research examines the application of rules or norms or is called normative juridical research. Using primary and secondary legal materials. The aim of this research is to philosophically examine the right to sue in environmental state administration cases. The results of the study reveal that the right to sue owned by individuals, business entities, environmental organizations is accompanied by requirements that must be met. The mechanism for resolving environmental state administrative disputes filed by the plaintiff in order to realize his right to sue begins with the registration of a lawsuit to the PTUN with its authority.